PERANAN DKPP DALAM PENEGAKAN INTEGRITAS PENYELENGGARA PEMILIHAN UMUM: Pemilihan Umum Di DKI Jakarta 2019 - Syahrul Mubarak (2022)
This thesis aims to examine the role of DKPP towards Election Organizers in the 2019 Election in DKI Jakarta by using the concept of Election Organizer Integrity. The method used is a qualitative approach with data collection techniques in the form of in-depth interviews with the Head of the Trial Section of the DKPP RI. The results of this thesis find that DKPP is tasked with maintaining the dignity of the Election Organizers not to commit acts of violation of the code of ethics or dishonesty. Unfortunately, it is still common for Election Organizers to commit these violations. DKPP's role is to conduct trials against those violators and, among others, DKPP also has a role, namely; Strengthening the Functions of the Regional Examination Team, Strengthening DKPP Institutions and Utilization of Complaints Facilities.